Cxcl8 (Interleukin-8) mediates neutrophil recruitment and behavior in the zebrafish inflammatory response - de Oliveira, Sofia (2013)
Neutrophils play a pivotal role in the innate immune response. The small cytokine CXCL8 (also known as interleukin-8 or IL-8) is known to be one of the most potent chemoattractant molecules which, among several other functions, is responsible for guiding neutrophils through the tissue matrix until they reach sites of injury. Unlike mice and rats that lack a CXCL8 homologue, zebrafish has two distinct CXCL8 homologues: Cxcl8-l1 and Cxcl8-l2. Cxcl8-l1 is known to be up-regulated under inflammatory conditions caused by bacterial or chemical insult but until now, the role of Cxcl8s in neutrophil recruitment has not been studied. Here, we show that both Cxcl8 genes are up-regulated in response to an acute inflammatory stimulus, and that both are crucial for normal neutrophil recruitment to the wound and normal resolution of inflammation. Additionally, we have analyzed neutrophil migratory behavior through tissues to the site of injury in vivo, using open-access phagocyte tracking software, PhagoSight. Surprisingly, we observed that in the absence of these chemokines, the speed of the neutrophils migrating to the wound was significantly increased in comparison to control neutrophils, although the directionality was not affected. Our analysis suggests that zebrafish may possess a sub-population of neutrophils whose recruitment to inflamed areas occurs independently of Cxcl8 chemokines. Moreover, we report that Cxcl8-l2 signaled through Cxcr2 for inducing neutrophil recruitment. Our study, therefore, confirms the zebrafish as an excellent in vivo model to shed light on the roles of CXCL8 in neutrophil biology.